DISCORDANT THYROID FUNCTION TESTS: DIAGNOSTIC CHALLENGES IN A PATIENT WITH A TSH-SECRETING PITUITARY ADENOMA - Chong, Pui Lin; Matali, Nur Husnina; Upadhyaya, Sunil (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Discordant Thyroid Function Tests (TFTs) may present a diagnostic challenge in clinical practice. Assay interference must be excluded before proceeding to further investigations. Rarely, the underlying diagnosis may be a TSH-secreting pituitary adenoma (TSHoma) or resistance to thyroid hormone (RTH). Making a diagnostic distinction between these two conditions is important as their clinical management varies significantly. CASE A 47-year-old engineer was referred to the Endocrine clinic with symptoms of hyperthyroidism and discordant TFTs. These symptoms improved with propranolol and carbimazole. Only his paternal aunt has a goitre on family history. On physical examination, there was no palpable goitre. His TFT was discordant before starting carbimazole [TSH 4.32 mIU/L (NR: 0.27–4.20), fT4 34.1 pmol/L (NR: 12.0–22.0), fT3 11.6 pmol/L (NR: 3.10–6.80)]. Discordance persisted despite using two different immunoassays after stopping carbimazole. Alpha-subunit was raised (2.47 IU/L; NR: 0.0–0.7). A pituitary MRI showed pituitary macroadenoma. Pituitary hormones were within normal limits except for an elevated IGF-1. An oral glucose tolerance test was inconsistent with acromegaly as nadir growth hormone was 0.8 mIU/L (0.27 g/L). Several tests distinguishing a TSHoma from RTH were unavailable, so the patient underwent a somatostatin test. Following octreotide, TSH was suppressed with low-normal free thyroid hormone levels, highly suggestive of a TSHoma. Our patient underwent an endoscopic transsphenoidal hypophysectomy. The histology report confirmed TSH and growth hormone-secreting adenoma. CONCLUSION The case illustrates challenges in establishing the diagnosis of a TSHoma with resource limitations and supports using intramuscular octreotide LAR as a diagnostic tool. Appropriate evaluation of discordant TFT is paramount to avoid unnecessary investigations and treatments. The somatostatin test can be useful and practical in differentiating TSHoma from resistance to thyroid hormone.